Современные миграционные процессы: обустройство и адаптация ранее депортированных крымских татар в Крыму - Прибыткова, И. (Социология: теория, методы, маркетинг, 2000)
The author has presented a new form (for Ukraine) of migration — repatriation of formerly deported people and used the empirical data of sociological research for interpretation and demonstration of specific aspects of migration processes theory. Let us remind our reader that migration processes theory was formed in the three-stage paradigm. The first stage, named potential migration, determines the next development stage, namely migration. At the third stage, migrants adapt to their new conditions of life and, in some period of time, the new settlers become old-timers. The research data on the last stage of return of formerly deported Crimean Tatars have been analysed in the article.